Empowering Learning Through Dialogue: The Impact of Parental Academic Socialization on Student Success in Indonesia - Lestari, Putri Ayu (Indonesian Scientific Publication, 2025)
Introduction & Objective: Parental involvement strongly influences student achievement. Among its forms, academic socialization—parents’ communication of educational values, goals, and expectations—plays a particularly important role. This study explores how academic socialization shapes student outcomes in Indonesia and compares its effects with other types of involvement. Methods: Data were collected from more than 2,000 secondary students in four provinces. Hierarchical linear modeling (HLM) and mediation analysis were used to test the effects of parental involvement, with cultural capital as a mediator. Results: Academic socialization showed the strongest positive effect on GPA, attendance, and aspirations (β = 0.42, p < .001), stronger than home- or school-based involvement. Cultural capital significantly mediated these relationships. Conclusion: Academic socialization is a strategic pathway for improving student success in Indonesia. Schools and policies should focus on strengthening parents’ ability to communicate academic goals and values, especially in low-SES communities.